2020
DOI: 10.21203/rs.3.rs-17690/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Attitude, Motivation and Planning of Breastfeeding; A cross Sectional Study among Jordanian Women.

Abstract: Abstract Background Antenatal women’s attitude and planning for breastfeeding are affected by their awareness and the support they receive. These are key factors that contribute to the trend variation in breastfeeding practice. This study aims to assess knowledge, attitude, support, and planning of breastfeeding among Jordanian women. Methods A face-to-face cross sectional semi-structured questionnaire survey was conducted among healthy women in the antenatal clinic and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The intervention doubled the number of mothers who began breastfeeding within the rst hour of delivery and those who exclusively breastfed their infants for 6 months. Increased understanding of behaviors related to breastfeeding practices was found to be assuring factor for enhancing breastfeeding in Jordan, according to recent Eastern Mediterranean studies (35,38).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The intervention doubled the number of mothers who began breastfeeding within the rst hour of delivery and those who exclusively breastfed their infants for 6 months. Increased understanding of behaviors related to breastfeeding practices was found to be assuring factor for enhancing breastfeeding in Jordan, according to recent Eastern Mediterranean studies (35,38).…”
Section: Discussionmentioning
confidence: 96%
“…Enhancing breastfeeding practices is a worldwide concern that was included among the Millennium Development Goals developed by the World Health Organization in the last decade (34,35). Investing in children's growth and development could theoretically drive the transformation endeavored for by 2030 under SDG3, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good knowledge and positive attitude of mothers about the bene ts of EBF plays important role for the continuation EBF until six months (9,10). A study in Jordan showed support and encouragement from husband and extended family members were associated with increased rate of EBF for six months (11), whereas mother's return to paid employment negatively impacted the duration of EBF (7,12,13). Employed women need to return to work before six months because paid employment is a necessity, not an option for many of them (14).…”
Section: Introductionmentioning
confidence: 99%
“…Good knowledge and positive attitude of mothers about the bene ts of EBF plays important role for the continuation EBF until six months (9,10). A study in Jordan showed support and encouragement from husband and extended family members were associated with increased rate of EBF for six months (11), whereas mother's return to paid employment negatively impacted the duration of EBF (7,12,13).…”
Section: Introductionmentioning
confidence: 99%